Aligning opportunity cost and net benefit criteria: the health shadow price - Eckermann, Simon (Frontiers in Public Health, 2024)
Given constrained health system budgets and many competing population health demands public health decision making requires comparing expected cost and health outcomes of alternative strategies and associated adoption and financing actions. Opportunity cost (comparing outcomes from best alternative use of budgets or actions in decision making) and more recently net benefit criteria (relative valuing of effects at a threshold value less costs) have been key concepts and metrics applied towards making such decisions. In an ideal world opportunity cost and net benefit criteria should be mutually supportive and consistent. However, that requires a threshold value to align net benefit with opportunity cost assessment. This perspective piece shows that using the health shadow price as the ICER threshold value for net benefit aligns net benefit and opportunity cost criteria for joint adoption and financing actions that arise with reimbursing any new strategy or technology under a constrained budget. For an investment strategy with ICER at the health shadow price Bc= 1/(1/n+1/d-1/m), the net benefit of reimbursing (adopting and financing) that strategy given an incremental cost effectiveness ration (ICER) of actual displacement, d, in financing, is shown to be equivalent to that of the best alternative actions, the most cost-effective expansion of existing programs (ICER=n) funded by contraction of least cost effective programs (ICER=m). Net benefit is appropriately positive or negative when below or above that threshold. Implications are discussed for creating pathways to optimal public health decision-making with appropriate incentives for efficient displacement as well as adoption actions and associated research.